PENGARUH KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT YANG DIMODERASI OLEH SIFAT KEPRIBADIAN AUDITOR - Dewi, Dian Komala (Jurnal Ilmiah Mahasiswa FEB, 2016)
Auditor personality is an interesting topic in the field of accounting considering the research on this topic is still rarely performed. The purpose of this study is to provide an empirical evidence with regard to the effect of the competency of auditors on audit quality, with a focus on the role of personality traits namely the big five personalities. Respondents of this study are auditors of public accounting firms in Malang. The analysis technique used to test the hypothesis is the modarated regressions analysis. The test results show that the competency of auditors has an effect on audit quality. In addition, only the personality traits of extraversion and neuroticism affects the relationship between competency of auditors and audit quality, but other personality traits such as openness to experience, conscientiousness, and agreeableness has no effect on such relationship. This indicates that the auditor's personality is an important factor to improve the quality of audits.Keywords: audit, personality, competency, audit quality